Broadband High-Efficiency Electromagnetic Orbital Angular Momentum Beam Generation Based on a Dielectric Metasurface - Zhansong Lin; Zhongling Ba; Xiong Wang (IEEE Photonics Journal)
Electromagnetic waves carrying orbital angular momentum (OAM) have motivated a wealth of applications. Achromatic or broadband OAM beams are preferred in many applications and have been extensively explored in previous research endeavors. In view of the low efficiency of the previous reported broadband OAM generators, this work proposes a metasurface composed of high-refractive-index dielectric resonators to achieve broadband OAM beam generation with high efficiency. An efficient method for designing the resonators is presented, which indicates that proper adjustment of the dimensions and rotation of the dielectric resonators can render broadband and high-efficiency full phase control. A broadband high-efficiency OAM generator is engineered based on the resonators from 18 to 28 GHz as a proof-of-concept example and validated by both simulation and experiments. Above 70% polarization conversion efficiency and above 65% operation efficiency are measured throughout the entire design band. Such structure provides an alternative mechanism for realizing broadband high-efficiency microwave, millimeter-wave, terahertz or optical OAM generation and can find potential applications in high-capacity communications and imaging.